Catalytic Decarboxylation of Palm Oil to Green Diesel over Pellets of Ni-CaO/Activated Carbon (AC) Catalyst Under Subcritical Water - Desy Septriana; Muhammad Mufti Azis; Joko Wintoko (ASEAN Journal of Chemical Engineering, 2023)
There has been a considerable in converting palm oil to green diesel. Green diesel is a hydrocarbon compound similar to conventional diesel fuel's components. It is expected to substitute conventional diesel fuel in diesel vehicle engines. The process of producing diesel is also called the deoxygenation process. One of the deoxygenation processes is decarboxylation. The current study evaluates the performance of Ni-CaO/AC catalyst in the form of pellets by mixing a powder Ni-CaO/AC catalyst and phenolic resin. The aim of this study namely to evaluate the performance pellets of Ni-CaO/AC catalyst in the decarboxylation of palm oil under sub-critical water. This research includes catalyst activity carried out by decarboxylation in subcritical water with temperature variations: 300, 310, 320, and 330 Â°C using pellets of Ni-CaO/AC catalyst. The decarboxylation products obtained were analyzed with Gas Chromatography-Mass Spectroscopy (GC-MS). The results obtained in this study showed that the highest percentage composition and selectivity of green diesel were obtained at a temperature of 330 Â°C, with values of 18.08 and 22.07, respectively. These results suggest that higher temperature promotes the hydrogenation-decarboxylation reaction of palm oil. Pellets of Ni-CaO/AC catalyst can increase the selectivity of green diesel if the phenolic resin is replaced with a binder that can provide physical strength to the catalyst but does not damage the function and cover much of the active surface area of the catalyst. We can conclude that pellets of Ni-CaO/AC catalysts have the potential to do hydrothermal decarboxylation if the increased operating condition.